Actualizing Communities of Practice (COPs) and Situated Learning for A Sustainable Eco-Village - Maria Victoria Pineda (Jurnal Sains & Teknologi Lingkungan, 2011)
An eco-village as defined by Robert Gilman is a “human-scale, full-featured settlement where you feel you know the others, and human activities are integrated with natural, biological systems.” Roland Mayerl argued that this maybe ideal, but there are huge challenges. He claims the challenges are at different levels—there is the physical layer that constitutes food production, animals, water and wastewater treatment. Other layers will be the built environment, the economic system and the governance in the village.This paper argues that one of the challenging layers is the human layer that was excluded in the modeling of many eco-village works. While there are many good models of an eco-village, sustainability will primarily be laid on the shoulders of the members of the community or the village for that matter. Sustainability should be espoused by the members of the eco-village. But how can sustainability be attained? What sustainability approach or strategy can be employed?“Communities of practice (COP) are formed by people who engage in a process of collective learning in a shared domain of human endeavor.“ (Wenger, 2004) COPs are concepts commonly applied in organizations and virtual communities. Using this approach together with periphery participation and situated learning, this paper presents a human-based model of a sustainable eco-village and some useful examples.The paper also argues that an eco-village necessitates the support of technology in enhancing and preserving the shared practices. Hence, use of social media deployed in the web is one of the recommended ways that also permit collective action among members of the eco-village.